Using Paraquat to Generate Anion Free Radicals and Hydrogen Peroxide in In Vitro : Antioxidant Effect of Vitamin E (2010)
ABSTRACT: The theoretical basis of reactive oxygen species and their impact on health issues are relatively easy tounderstand by biomedical students. The detection of reactive oxygen species requires expensive equip-ment, the procedures are time consuming and costly, and the results are hard to interpret. Moreover,cause-and-effect relationships in the living system are not so evident. In this report, we adapted a two-step procedure to detect anion superoxide radicals and hydrogen peroxide generation in lymphocytesexposed to paraquat by using nitroblue tetrazolium salt and dihydrorhodamine, respectively. Also, a two-step assay was performed to evaluate lymphocyte viability and nuclei morphologic changes on paraquatexposure for 1 and 24 hours incubation time by using trypan blue exclusion assay and acridine orange/ethidium bromide staining technique, respectively. Vitamin E was used as antioxidant to inhibit the dele-terious effects of paraquat on cells. Students learned how to (i) design and perform experiments in thelaboratory, (ii) read critical scientific literature, and (iii) discuss and contrast relevant information aboutreactive oxygen species as causative agents of cell death phenomenon